MEASURING THE EFFICIENCY OF TOURISM COMPANIES LISTED ON BIST BY DATA ENVELOPMENT ANALYSIS METHOD (Third Sector Social Economic Review, 2020)
The purposes of this study are to determine the effects of fluctuations, and to elicit the tourism firms' effectiveness since 2016 in the Turkish market, and to propose suggestions for improvements. In these scopes, between 2016 and 2019, the annual reports and the financial statements of 11 tourism firms that are traded in BIST were examined. Data Envelopment Analysis (DEA) that is a non-parametric mathematical programming method, was used to measure the efficiencies of firms. Firms were analyzed with the BCC method that is based on the assumption of variable returns according to the scale, being input-oriented. As a result of the analysis, the targeted input values were determined so that the firms could reach the data output amount, and improvement values that would require a nearly half reduction in the available input amounts were calculated. A firm that effectiveness cannot reach the targeted input value should reduce its expenses based on its activities. These improvements are related to firm size and technical issues. However, it was determined that it is necessary a cut at the investment budget compared to the firm’s income and profit obtained. When activity-based inputs that are regulated according to the BCC method improvement tables can serve as a guide for ineffective decision-making units of the firm.
Keywords: BIST Tourism Firms; Efficiency Measurement; Data Envelopment Analysis (DEA)